Analisis Rancangan Assesmen Kompetensi Minimum (AKM) Numerasi Program Merdeka Belajar - Dini Andiani; Mimi Nur Hajizah; Jarnawi Afgani Dahlan (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2021)
The Minimum Competency Assessment (AKM) Numeration of the Program Merdeka Belajar is one of the components that will be tested in 2021 as a substitute for the National Examination (UN). The purpose of writing this article is to provide input on the Minimum Competency Assessment (AKM) design, especially in the field of numeracy related to content and cognitive processes. Writing this article is done using a qualitative approach through document review in the form of laws, government regulations, books and related journal articles. The result of this examination is the need for a Numeration Minimum Competency Assessment (AKM) design which contains the contents of numbers, algebra, geometry, statistics and odds as stated in Permendiknas No. 21 of 2016.